2020
DOI: 10.1155/2020/5457049
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ubiquitin-Proteasome Pathway and Autophagy-Lysosome Pathway in Cerebral Ischemia

Abstract: The ubiquitin-proteasome pathway and autophagy-lysosome pathway are two major routes for clearance of aberrant cellular components to maintain protein homeostasis and normal cellular functions. Accumulating evidence shows that these two pathways are impaired during cerebral ischemia, which contributes to ischemic-induced neuronal necrosis and apoptosis. This review aims to critically discuss current knowledge and controversies on these two pathways in response to cerebral ischemic stress. We also discuss molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 110 publications
0
30
0
Order By: Relevance
“…Stroke, an acute cerebrovascular disease, is an important contributor to mortality and permanent disability worldwide [1,2]. Epidemiological data showed that ischemic strokes account for approximately 87% of these incidences [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke, an acute cerebrovascular disease, is an important contributor to mortality and permanent disability worldwide [1,2]. Epidemiological data showed that ischemic strokes account for approximately 87% of these incidences [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This kind of blood flow recovery can lead to irreversible damage such as brain cell necrosis, cell swelling, and tissue with heterogeneous blood flow [ 14 ]. According to a large number of studies on CI/R injury in recent years, CI/R injury has been proved to be a key factor leading to brain injury, and the involvement of neuroinflammation and oxidative stress in the pathophysiological process of CI/R injury has also been confirmed [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that the activation of AMPK mediates the autophagy-related neuroprotection [ 51 - 53 ]. In addition, the number of misfolded proteins surges in IS, which overloads the ubiquitin-proteasome pathway and disrupts the balance between the ubiquitin-proteasome and autophagy pathway [ 9 ]. Increased BAG3 and HDAC6 initiate the conversion from the ubiquitin-proteasome pathway to the autophagy pathway [ 54 ], which leads to the initiation of the autophagy pathway in IS (Fig.…”
Section: Autophagy Pathway In Ischemic Strokementioning
confidence: 99%
“…Autophagy is a natural, regulated process which helps cells to eliminate unnecessary or dysfunctional components, including long-lived proteins, insoluble proteins, and even whole organelles [ 8 , 9 ]. Autophagy is composed of microautophagy, macroautophagy, and chaperone-mediated autophagy (CMA) according to the way of cargo delivery to the lysosomes.…”
Section: Introductionmentioning
confidence: 99%